PPARα Ligands as Antitumorigenic and Antiangiogenic Agents. (14th August 2008) - Pozzi, Ambra; Capdevila, Jorge H.
Abstract : Peroxisome proliferator-activated receptors (PPARs) belong to the nuclear receptor family of ligand-activated transcription factors. This subfamily is composed of three members—PPARα, PPARδ, and PPARγ —that differ in their cell and tissue distribution as well as in their target genes. PPARα is abundantly expressed in liver, brown adipose tissue, kidney, intestine, heart, and skeletal muscle; and its ligands have been used to treat diseases such as obesity and diabetes. The recent finding that members of the PPAR family, including the PPARα, are expressed by tumor and endothelial cells together with the observation that PPAR ligands regulate cell growth, survival, migration, and invasion, suggested that PPARs also play a role in cancer. In this review, we focus on the contribution of PPARα to tumor and endothelial cell functions and provide compelling evidence that PPARα can be viewed as a new class of ligand activated tumor "suppressor" gene with antiangiogenic and antitumorigenic activities. Given that PPAR ligands are currently used in medicine as hypolipidemic drugs with excellent tolerance and limited toxicity, PPARα activation might offer a novel and potentially low-toxic approach for the treatment of tumor-associated angiogenesis and cancer.